Pendampingan Pencegahan Virus Covid-19 Terhadap Relawan Gugus Tugas Covid-19 di Pondok Pesantren Fathul Hidayah Pangean - Saifudin; Rahmah, Regita Nur Fajar (TAAWUN, 2022)
Assistance in Preventing the Covid-19 Virus Against Volunteers of the Fathul Hidayah Pangean Islamic Boarding School aims to help students, teachers and caregivers to cope with the prevention and spread of the Covid-19 virus in the hope that the students are not exposed to the virus that is hitting this country. This type of research is community service. The method of activities carried out through several stages through consolidation, socialization, and education, as well as evaluation of activities and the sustainability of activities. The programs that have been implemented include strengthening material on the prevention of the covid-19 virus and various series of volunteer work programs for the COVID-19 task force at the Fathul Hidayah Islamic Boarding School in accordance with the initial objectives. Participation and support from the pesantren is quite high, where the students are actively involved in implementing the program so that the community can take full advantage of it.